Cancer oesophagus: is sequential chemo radiation better in elderly patients or patients with severe dysphagia? - Rathore, Narendra; Bana, Poonam Chand; Shukla, Arvind Kumar; Jain, Abhay Kumar; Rajpurohit, Vikram Singh; Intodia, Kiran (International Journal of Research in Medical Sciences, 2017)
Background:This study was conducted to analyse the local control, regional control and toxicities of sequential versus concurrent chemo radiation in the patients of oesophageal cancer especially in elderly. Methods: A total of newly diagnosed 50 patients were randomized in concurrent and sequential arm. Two courses of 3 weekly chemotherapy (Cisplatin and 5-FU based) were given concurrently and three courses of same chemotherapy were given neoadjuvantly with EBRT (44 Gys) respectively in randomised arms. HDR-ICBT (2 fractions of 5 Gy) delivered after two weeks of completion of EBRT in both arm. Results: Concurrent arm had higher incidence of grade III+IV overall all toxicity especially in elderly patients or patients that presented with grade IV or higher dysphagia. Other haematological and non-haematological toxicities were equal in both arms. Complete response at both primary and mediastina was higher in concurrent arm but there was no statistically significant difference. Conclusions: Our data suggest that if a patient can tolerate the combination of chemotherapy and radiation, this approach offers superior results but at the cost of higher incidence of severe toxicities especially in patients with grade IV or higher dysphagia or elderly patients. So this group could be treated with sequential chemo radiation.